Infestation, community structure, seasonal fluctuation and climate-driven dynamics of mites on small mammals at a focus of scrub typhus in southwest China - Yin, Peng-Wu; Lv, Yan; Guo, Xian-Guo; Song, Wen-Yu; Fan, Rong; Zhao, Cheng-Fu; Zhang, Zhi-Wei; Zhao, Ya-Fei; Dong, Wen-Ge; Jin, Dao-Chao (Frontiers in Veterinary Science, 2025)
ObjectiveRodents and other sympatric small mammals serve as reservoir hosts for zoonotic diseases including scrub typhus and hemorrhagic fever with renal syndrome (HFRS), with their ectoparasitic mites (chiggers and gamasid mites) acting as vectors. This 12-month study investigated mite infestation, community structure, seasonal dynamics, and climatic drivers on small mammal hosts in Jingha, southern Yunnan, China–a known scrub typhus and HFRS.MethodsWe calculated infestation metrics (prevalence [PM], mean abundance [MA], mean intensity [MI], constituent ratio [Cr]) and community indices (richness [R], Shannon-Wiener diversity [H], Pielou evenness [E], Simpson dominance [D]). Generalized additive models (GAMs) analyzed spatiotemporal and climatic patterns.ResultsFrom 2,424 small mammal hosts (15 species), we collected 142,471 mites (158 species). Chiggers (109 species, 109,093 individuals) significantly outnumbered gamasid mites (49 species, 33,378 individuals; P < 0.001) and showed greater richness (R = 9.31 vs. 4.61), diversity (H = 2.13 vs. 1.97). Rattus andamanensis was the dominant host. Chigger infestation (PM = 86.14%, MA = 45.01, MI = 52.25) significantly exceeded gamasid mites (PM = 67.16%, MA = 13.77, MI = 20.50; P < 0.001), particularly on female and adult hosts. Four species dominated (Cr = 65.40%): chiggers Walchia micropelta, Ascoschoengastia indica, Leptotrombidium deliense, and gamasid mite Laelaps nuttalli. Primary vectors among 23 species included chiggers L. deliense, A. indica, L. scutellare, and gamasid Laelaps echidninus (Cr = 38.46%).ConclusionCommunity indices fluctuated monthly without distinct peaks, while dominant species abundances varied significantly. Climatic factors exerted species-specific effects: L. deliense peaked in July (30.0 mites/host; 95% CI: 29.2–30.8) coinciding with maximal temperatures, while A. indica peaked in August (25.1 mites/host; 95% CI: 24.5–25.8), lagging peak rainfall. Non-overlapping confidence intervals indicated temporal niche separation between species. Mite-mite networks revealed positive intragroup correlations but no significant intergroup correlations. Host-mite networks demonstrated low host specificity: individual hosts harbored multiple mite species, and individual mite species parasitized multiple hosts. High mite abundance, co-occurrence of multiple vector species, and low host specificity collectively elevate transmission risks and persistence of scrub typhus and HFRS.